Usefulness of comprehensive targeted multigene panel sequencing for neuromuscular disorders in Korean patients - Jihye Park; Hyun Mi Oh; Hye Jung Park; Ah‐Ra Cho; Dong‐Woo Lee; Ja‐Hyun Jang; Dae‐Hyun Jang (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background Multigene panel sequencing (MGPS) is the first‐line option in diagnostic testing for genetically heterogeneous but clinically similar conditions, such as neuromuscular disorders (NMDs). In this study, we aimed to assess the utility of comprehensive NMD MGPS and the need for updated panels. Methods All patients were analyzed by either of two versions of the NMD MGPS and by chromosomal microarray and karyotype testing. Four patients with negative NMD MGPS results underwent whole exome sequencing. Results In total, 91 patients were enrolled, and a genetic diagnosis was made in 36 (39.6%); of these, 33 were diagnosed by the comprehensive NMD MGPS, two were confirmed by chromosomal microarray, and one was diagnosed by whole exome sequencing. For MGPS, the diagnostic yield of Version 2 (19/52; 36.5%) was a little higher than that of Version 1 (14/39; 35.9%), and one gene identified in Version 2 was not included in Version 1. A total of 36 definitive and nine possible causative variants were identified, of which 17 were novel. Conclusion A more comprehensive panel for NMD MGPS can improve the diagnostic efficiency in genetic testing. The rapid discovery of new disease‐causing genes over recent years necessitates updates to existing gene panels.